The literature police: apartheid censorship and its cultural consequences - McDonald, P (2009)
This website is a supplement to Peter D. McDonald’s book The Literature Police: Apartheid Censorship and its Cultural Consequences, which was first published by Oxford University Press in February 2009. It is intended for anyone curious to know more about the subject and for those interested in doing further research into the vast topic of apartheid censorship.